Hepatitis C Virus Genotype Distribution in Forensic Cases - (:unkn) unknown (GALENOS YAYINCILIK, 2020)
Objectives: In this study, we aimed to determine the hepatitis C virus (Hai) genotype and subtypes in blood samples that were determined by polymerase chain reaction (PCR) in autopsy cases. Materials and Methods: The blood samples of autopsy cases that was sent to serological screening to post-mortem microbiology laboratory between years 2014-2018 were recruited. Forty blood HCV-PCR positive autopsy cases were further evaluated including demographic, clinic, laboratory and autopsy features. Results: Thirty-five 35 (87.5%) of the patients were male and 5 (12.5%) were female. The mean age of the patients was 43.1 +/- 11.8 years. Of the 40 cases, 18 (45%) were Turkish citizens and 16 (40%) were other nationals. The identity information of 6 cases (15%) could not be determined. Among 40 HCV-positive cases by PCR, the genotype 3 was determined in 11 (27.5%) of the cases, genotypel a in 9 (22.5%) cases, genotype-1b in 7 (17.5%) cases, genotype-2 in 2 (5%) cases and genotype-4 in 2 (5%) cases. In 9 (22.5%) cases, the genotype could not be determined. Conclusion: The most common HCV genotype in our study population was determined to be genotype-3 and the most common genotype in Turkish origin cases was found to be genotype-1a. Postmortem PCR analysis for HCV infection is feasible and relevant for demonstrating the ongoing infections at death. Monitoring the change in HCV genotype distribution is critical for the development of effective strategies for HCV elimination.
Keywords: Hepatitis C Virus; genotype; molecular epidemiology; post-mortem microbiology; HCV GENOTYPES; INFECTION; PREVALENCE; ANTALYA; DISEASE